1984
DOI: 10.2320/matertrans1960.25.761
|View full text |Cite
|
Sign up to set email alerts
|

On the Phosphorus Distribution between Slag and Metal

Abstract: It has been shown on the dephosphorization ofliquid iron that the values oflog ƒÁP2o•B or log(ƒÁP2o5/ ƒÁ5Feo)at 1873K calculated from the data independently investigated and recently reported are closely related to those of the theoretical optical basicity for each slag, and these relations can be expressed in a simple single line for the case, in which slag constituents are lime, sodium oxide and several other materials. The symbol"ƒÁ"signifies the activity coefficient of slag components in mole fraction unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(75 citation statements)
references
References 13 publications
2
72
1
Order By: Relevance
“…The results indicated that the degree of viscosity increase with increasing P2O5 content was greater at lower basicity. It is consistent with the previous study, 19,20) which reported that the activity coefficient of P2O5 in slag melts was smaller at a higher basicity, and this resulted in a weak influence on the viscosity. Figure 6 shows the viscosity variation of the slag melts without P2O5 with varying basicity.…”
Section: Viscosity Of the Ti-bf Slagssupporting
confidence: 82%
“…The results indicated that the degree of viscosity increase with increasing P2O5 content was greater at lower basicity. It is consistent with the previous study, 19,20) which reported that the activity coefficient of P2O5 in slag melts was smaller at a higher basicity, and this resulted in a weak influence on the viscosity. Figure 6 shows the viscosity variation of the slag melts without P2O5 with varying basicity.…”
Section: Viscosity Of the Ti-bf Slagssupporting
confidence: 82%
“…Molloseau and Fruehan [7] and Sarma [8] also observed a similar effect of FeO in the slag on mass transfer coefficient of FeO but did not offer a detailed explanation. From Figure 5, it is interesting to note that comparing data for high and low liquid fraction slags, they scale in reasonable approximation to the ratio of liquid fraction.…”
Section: A Mass Transfer Of Feo In the Slagmentioning
confidence: 86%
“…8,12,[21][22][23][24] In order to compare the present result with those of previous investigators, the theoretical optical basicity was applied and the values for the optical basicities were taken from the literature. 25) The relationship between phosphate capacities in logarithmic form and optical basicity is shown in Fig.…”
Section: Mgo Solubilities In the Caomentioning
confidence: 99%